PENGATURAN MEDIASI PENAL PASCA REGULASI KEADILAN RESTORATIF DI KEPOLISIAN, KEJAKSAAN, DAN MAHKAMAH AGUNG - Hanifah Febriani; Carissa Maharani; Sadida Amalia Izzatul Haq (Universitas Muhammadiyah Mataram, 2023)
Penal mediation brings benefits to victims, perpetrators, or society. Penal mediation also takes into account the practical needs of settling cases, and can bring about a fast, simple, low-cost trial. Even though the settlement of cases by mediation is quite familiar in the society, previously the settlement of criminal cases by mediation did not have a sufficiently strong legal basis except for cases involving children in conflict with the law. Currently, penal mediation has been regulated in Prosecutor's Regulations Number 15 of 2020, Badan Peradilan Umum Decree Number: 1691/DJU/SK/PS.00/12/2020 and Police regulation Number 8 of 2021. Since it is left to each institution, differences in arrangements and the scope of implementation of penal mediation is inevitable. This research is a normative research using data from library research. The data were analyzed qualitatively by using a statutory approach and a conceptual approach. This study found that there were differences in penal mediation arrangements in each law enforcement institution. These differences are related to the legal basis used, types of cases, exceptions to types of cases, the role of law enforcement officials, differences in the mechanisms for peace agreements and termination of cases as well as arrangements related to victims' recovery.